Mesoscopic origin of ferroelectric-ferroelectric transition in BaTiO3: Orthorhombic-to-tetragonal domain evolution. (1st April 2020) - Hershkovitz, Asaf; Johann, Florian; Barzilay, Maya; Hendler Avidor, Alon; Ivry, Yachin
Abstract : Ferroelectric materials are the core of common technologies, such as medical ultrasound, mobile-phone antennae and low-power memory devices. The technological interest in ferroelectrics stems from the existence of switchable mesoscale polarization domains. Hence, understanding the origin of ferroelectric functionality requires realization of the domain dynamics during a ferroelectric transformation. However, domain dynamics characterization at the mesoscale is typically too slow with respect to the abrupt ferroic transition. Using scanning probe microscopy with 15-mK thermal-, and deep-submicron spatial- resolution, we realized the domain dynamics during an orthorhombic-to-tetragonal transition in the seminal ferroelectric BaTiO3 . We show that the transition comprises four distinguishable mechanisms. The dominant mechanism is a step-by-step progression of a tetragonal-domain wavefront into the orthorhombic phase. This progression is accompanied by ripple-like surface irregularities. Small island domains that remained orthorhombic diffuse then slowly after the wavefront progression. Finally, the resultant tetragonal domains equilibrate by coalescing in a constant-speed. These observations, which are accompanied by quantitative data, bridge between existing macroscopic and microscopic models regarding the nature of ferroelectric transitions, showing the mesoscale origin of ferroelectricity. Abstract : Image, graphical abstract